The high tide club [compact disc, unabridged] - Andrews, Mary Kay, 1954- (Macmillan Audio, 2018)
Hired by a millionaire from a vast barrier island home, an attorney learns the story of the new client's now-deceased friends, her determination to protect the land, clues about an unsolved murder, and her plans for heirs and descendants.